Single mRNA detection of Wnt signaling pathway in the human limbus. (April 2023) - Bonnet, Clémence; Ruiz, Maxime; Gonzalez, Sheyla; Tseng, Chi-Hong; Bourges, Jean-Louis; Behar-Cohen, Francine; Deng, Sophie X.
Abstract: Limbal epithelial stem/progenitor cells (LSCs) are adult stem cells located at the limbus, tightly regulated by their close microenvironment. It has been shown that Wnt signaling pathway is crucial for LSCs regulation. Previous differential gene profiling studies confirmed the preferential expression of specific Wnt ligands (WNT2, WNT6, WNT11, WNT16) and Wnt inhibitors (DKK1, SFRP5, WIF1, FRZB) in the limbal region compared to the cornea. Among all frizzled receptors, frizzled7 (Fzd7) was found to be preferentially expressed in the basal limbal epithelium. However, the exact localization of Wnt signaling molecules-producing cells in the limbus remains unknown. The current study aims to evaluate the in situ spatial expression of these 4 Wnt ligands, 4 Wnt inhibitors, and Fzd7. Wnt ligands, DKK1, and Fzd7 expression were scattered within the limbal epithelium, at a higher abundance in the basal layer than the superficial layer. SFRP5 expression was diffuse among the limbal epithelium, whereas WIF1 and FRZB expression was clustered at the basal limbal epithelial layer corresponding to the areas of high levels of Fzd7 expression. Quantitation of the fluorescence intensity showed that all 4 Wnt ligands, 3 Wnt inhibitors (WIF1, DKK1, FRZB), and Fzd7 were highly expressed at the basal layer of the limbus, then in a decreasing gradient toward the superficial layer ( P  < 0.05). The expression levels of all 4 Wnt ligands, FRZB, and Fzd7 in the basal epithelial layer were higher in the limbus than the central cornea ( P  < 0.05). All 4 Wnt ligands, 4 Wnt inhibitors, and Fzd7 were also highly expressed in the limbal stroma immediately below the epithelium but not in the corneal stroma ( P  < 0.05). In addition, Fzd7 had a preferential expression in the superior limbus compared to other limbal quadrants ( P  < 0.05). Taken together, the unique expression patterns of the Wnt molecules in the limbus suggests the involvement of both paracrine and autocrine effects in LSCs regulation, and a fine balance between Wnt activators and inhibitors to govern LSC fate. Highlights: Expression of FZD7, four Wnt ligands and DKK1 decrease from the basal towards the superficial epithelial layer in the limbus. WIF1 and FRZB expression are clustered at the limbal basal epithelial layer in the areas of high level of FZD7 expression. Wnt signaling molecules are expressed in the limbal stem cells (LSCs) and limbal stroma, suggesting that both paracrine and autocrine Wnt signaling are involved in LSC regulation. Wnt molecules involved in the canonical and non-canonical Wnt pathways co-exist in the LSC niche, supporting the involvement of both Wnt pathways in LSCs regulation.